(untitled) (Journal of Philosophy Culture and Political Science, 2018)
In this article taxes about issues that have increasedin our country, most of them haven’t found the real decision yet. Over the last 20 yers among the population there have been theologians and Islamists who startedto persuade other to the kind. Kazakhstan is a secular state, that means, religion and state are separate in it.That means government doesnot interfere in religious affairs, and religion lives according to their principials and perform their own duties. The government doesnot interfere in the relationship between citizens and God, however can intervene in religious matters if this concerns the public interest. For instance, if any of the religious associations, even if legally registered, encroach on government integrity and symbolism, then the government has the right to stop it. On the oter hans, if a person in some public places cannot profess his religious duties, then the government, in accordance with the law on «freedom of religion», have to protect his rights. Religious associations which are not so much in our country shouldn’t let government development and prosperity. Our country has been practicing interfaith relations for several years, which is an exemple for the entire world, therefore it is important to know the value of world and traditional religions on a scientificlevel in a secular society. Key words: confession, secularism, concept, freedom of religion, dogma, globalization.